Building Waqf Awareness for Improving Orphans' Education through Productive Waqf Education - Gamon, Alizaman Dumangcag; Hidayati, Nuril; Utama, Yopi Yudha; Muttaqin, Amrul; Syakur, Ahmad; Kholik, Jamaludin A.; Fauza, Nilna; Hamida, Ulfi Dina; Zunaidi, Arif; Puspitaningrum, Ririn Tri; Mushlihin, Imam Annas (Welfare : Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to increase public awareness and understanding of the importance of productive waqf management in supporting orphan education. Based on existing data, orphan education in Indonesia still faces major challenges in terms of funding, so economic empowerment efforts are needed through productive waqf. This activity was carried out through seminars and training based on service learning and ABCD (Asset-Based Community Development), which involved speakers from waqf experts and sharia financial practitioners. Participants consisted of academics, waqf managers, and community leaders. The activity began with a socialization of the concept of productive waqf, followed by a simulation of waqf asset management planning. The results of the activity showed a significant increase in participant understanding, with 85% of participants claiming to be able to design a productive waqf management model for orphan education. This activity successfully introduced waqf-based solutions as an economic empowerment instrument to support orphan education in a sustainable manner.